Notas al texto de De rebus gestis Caroli V de Juan Ginés de Sepúlveda (Libros 16-18) - Capela, Juan (Exemplaria Classica, 2009)
In this article the author presents and discusses, from the point of view of the textual critique, a selection of passages of Juan Ginés de Sepúlveda’s De rebus gestis Caroli V, belonging to the books XVI-XVIII of this work, recently edited by the author.